Media Tiktok dalam Meningkatkan Kosakata Bahasa Jerman - Maria Teliana Sum; Mantasiah R (Phonologie : Journal of Language and Literature, 2023)
Abstract. This research is a Quasi-Experimental design (non-equivalent design) which aims to find out data and information on the effectiveness of TikTok media in increasing the German vocabulary of class XI students at SMA Negeri 14 Makassar. The population of this research were students of class XI Social Sciences at SMAN 14 Makassar, totaling 70 students from two classes. The sample in this research was selected randomly (random sampling), namely students in class XI IPS 3 as an experimental class, totaling 35 students, and class XI IPS 4 as a control class, totaling 35 students. The research data were analyzed using the t-test. The results of the data analysis showed that ????ℎ???????????????????? 12.75 > ttable 1.998 at a significant level of 0.05. The results indicate that TikTok media is effective in increasing the German vocabulary of class XI students of SMA Negeri 14 Makassar.Keyword: Effectiveness, Media, TikTok, Vocabulary